Technology Commercialization and Marketing Products - Kumar, Puneet; Singh, R. P. (Indian Farming, 2015)
Livestock sector holds key to overcome the future unemploymentproblems in rural youth. Business incubation for commercialization of veterinary and animal science technologies through organizedintellectual property rights management and benefits sharingsystem and creating self employment through livestock entrepreneurship development will remain the priority areas for the Indian Veterinary Research Institute.